Diagnostic accuracy and feasibility of depression screening in spinal cord injury: A systematic review. (30th September 2019) - Titman, Rebecca; Liang, Jason; Craven, B. Catharine
Abstract : Context: Individuals with spinal cord injury or disease (SCI/D) are at increased risk of depression, which is associated with poor short- and long-term outcomes. Accurate diagnosis is complicated by overlapping symptoms of both conditions, and a lack of consensus-derived guidelines specifying an appropriate depression screening tool. Objective: To conduct a systematic review to: (1) identify the diagnostic accuracy of established depression screening tools compared to clinical assessment; and, (2) to summarize factors that influence feasibility of clinical implementation among adults with SCI/D. Methods: A systematic search using MEDLINE, EMBASE, PsycINFO, CINAHL and the Cochrane databases using the terms spinal cord injury, depression or mood disorder, and screening or diagnosis identified 1254 initial results. Following duplicate screening, five articles assessing eight screening tools met the final inclusion and exclusion criteria. Measures of diagnostic accuracy and feasibility of implementation were extracted. The Quality Assessment Tool for Diagnostic Accuracy Studies 2 (QUADAS-2) was used to assess study quality. Results: The Patient Health Questionnaire-9 (PHQ-9) had the highest sensitivity (100%), and specificity (84%). The 2-item version, the PHQ-2, comprised the fewest questions, and six of the eight tools were available without cost. Utilizing the QUADAS-2 tool, risk of bias was rated as low or unclear risk for all studies; applicability of the results was rated as low concern. Conclusion: The PHQ-9 is an accurate and feasible tool for depression screening in the adult SCI/D population. Future studies should evaluate the implementation of screening tools and the impact of screening on access to mental health interventions.